Trajetórias de preparação, inserção e permanência no ensino superior de mulheres bolsistas do Programa de Educação Tutorial (PET) da UFRB - Santos, Jaiana da Silva (2021)
The objective of this research is to analyze the trajectories of preparation, insertion and permanence in higher education of women scholarship holders from the Tutorial Education Program (PET) at UFRB. It is based on the following theoretical perspectives: student affiliation (COULON, 2008); student affiliation and permanence (SOUZA; SANTOS, 2014); university youth (CARNEIRO;SAMPAIO, 2011; LARANJEIRA; IRIART; RODRIGUES, 2016); transition to adult life (PIMENTA, 2017; MELLO, 2005); scientific research and university education (BRIDI, 2004); socialization processes (MINAYO, 2011; SETTON, 2011; CAMPOS, 2011; FARIA, 2017; BOURDIEU, 2002; SAFFIOTI, 2011; SILVA, 2012; FARIA, 2018; ROSA, 2015; youth and youth condition (DAYRELL, 2007; DURAND; ALVES, 2015); rural youth (CARNEIRO, 2005; WEISHEIMER, 2013); future projects (GRACIOLI, 2016; LECCARDI, 2005; NONATO, 2013). This is a qualitative research, with the support of quantitative data, which used questionnaires and semi-structured interviews with six PET scholarship holders as instruments of data production. The empirical context chosen is UFRB because it is an institution of a multicampi nature and has a significant contribution to the migration process, as it attracts students from different municipalities and states. The results showed that participation in PET contributes to higher quality academic and professional training, in addition to functioning as a support for permanence. As they were interviewed from popular classes, mostly from rural areas, and had long-term schooling trajectories, the fact that they were all students in courses in the areas of exact sciences and engineering, made it possible to understand how much women inserted in the so-called male contexts still face challenges to be accepted in these spaces.